Unlocking Vellore's water future: Integrated hydrogeochemical research aligns with SDGs 6, 12, and 13 - Sakshi Dange; Kumaraguru Arumugam; Sai Saraswathi Vijayaraghavalu (Results in Engineering)
Groundwater contamination is a critical issue in semi-arid regions, with significant implications for agriculture and human health. This study evaluates groundwater quality in the Vellore region, Tamil Nadu, India, using a combination of hydrogeochemical indices and GIS-based spatial analysis. A total of 171 groundwater samples were analysed for key parameters, including pH, TDS, nitrates, fluoride, and heavy metals. The Water Quality Index ranged from 42 to 175, with 45 % of the samples classified as poor or unsuitable for drinking purposes due to high nitrate, fluoride, and heavy metal concentrations. Similarly, the Pollution Index of Groundwater ranged from 0.4 to 4.5, with 60 % of samples indicating moderate to severe pollution, particularly in industrial and agricultural zones near the Palar River bed. The spatial analysis identified contamination hotspots, revealing that groundwater in urbanised areas and agricultural regions is unsuitable for both drinking and irrigation. High salinity and toxicity levels were found to adversely affect soil fertility, crop yields, and public health, posing risks such as methemoglobinemia, skeletal fluorosis, and long-term exposure to carcinogenic elements. The findings emphasise the urgent need for targeted mitigation strategies, including stricter industrial effluent controls, sustainable agricultural practices, and community-based monitoring programs. By providing actionable insights, this study advances the Sustainable Development Goals (SDG) 6 (Clean Water and Sanitation) and SDG 12 (Responsible Consumption and Production), offering a framework for sustainable groundwater management to improve agricultural productivity and safeguard human health.